KELLY, Aidan A. A Tapestry of the craft: A History of the Craft in America. Vol. 1. Tacoma, WA: Hierophant Wordsmith Press, 2014, 162p., ISBN: 9781499192643 - Terzetti Filho, Celso Luiz (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2016)
As tramas subjetivas de uma tapeçaria histórica Resenha de KELLY, Aidan A. A Tapestry of the craft: A History of the Craft in America. Vol. 1. Tacoma, WA: Hierophant Wordsmith Press, 2014, 162p., ISBN: 9781499192643